Intellectual Dimensions of Architectural Murals Art in Ancient Iraq (Pottery and Glazes) (Al-Academy, 2017)
. Mesopotamian art is thase mployed all around him into forms for artistic purposes and different con not at ions help him to understand the world around him and customized for their interestsThe mural architectural art has distinguished traits that made it promote to the rank of the prominent arts that have been employed by the Mesopotamian human to relate to the world the heroic deeds and exploits of that civilization ,that formed greatest and most splendid wonderful works that still illustrious and outstanding till nowadays .The mural architectural art of pottery and glazed considered one of the most ancient wonders of Mesopotamian creation in Old Iraq .The best quintessence of mural architectural art (pottery ,glazed )has been found in Al-Warkaa epoch and its significances ,since the dawn of history . Hence we checked his goal included:To recognize the intellectual dimensions of the mural art in Old Iraq and to employ them into the architecture .The research could be identified by the samples that represented by the intellectual dimensions of the Old Iraq mural architectural (pottery, glazed)from the period (3500 B.C-539 B.C.),since samples of mural arts have been chosen intentionally to serve the aim of the research .The researcher had chosen (3)samples of the mural Glazed pottery works .The theoretical framework Bembages:1-dimensional intellectual in the old Iraq. 2-artistic composition in the old Iraq.The researcher has con cludedher research with set of important results:The intellectual existence has related to the civilized period for historical epochs in a structure considered related to the functional role that in turn,Cosmic concepts that has made the image of the new reality and quoted the evolution of the philosophy of the state, and hugged form past, present and future in the form of shorthand symbols form, as in the sample (3(.